The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.neuroscience.2010.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and time-dependent benefits to learning and memory

Abstract: While it is well established that exercise can improve cognitive performance, it is unclear how long these benefits endure after exercise has ended. Accordingly, the effects of voluntary exercise on cognitive function and brain-derived neurotrophic factor (BDNF) protein levels, a major player in the mechanisms governing the dynamics of memory formation and storage, were assessed immediately after a 3-week running period, or after a 1-week or 2-week delay following the exercise period. All exercised mice showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
214
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(231 citation statements)
references
References 45 publications
(62 reference statements)
9
214
0
8
Order By: Relevance
“…Unlimited access to voluntary wheel running generally improves memory in C57BL/6J mice [36,37]. The lack of behavioural and cognitive effects of intermittent wheel running in our study raises the question of whether there are optimal levels of exercise for behavioural changes to occur.…”
Section: Intermittent Voluntary Wheel Running Does Not Alter Behavioumentioning
confidence: 56%
“…Unlimited access to voluntary wheel running generally improves memory in C57BL/6J mice [36,37]. The lack of behavioural and cognitive effects of intermittent wheel running in our study raises the question of whether there are optimal levels of exercise for behavioural changes to occur.…”
Section: Intermittent Voluntary Wheel Running Does Not Alter Behavioumentioning
confidence: 56%
“…Various protocols of differing intensities of exercise can also lead to different effects on the neurological function (40). Furthermore, based on learning definition, relatively stable are as the learning aspects.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study it was found that inhibition of BDNF during running prevents the enhanced memory function associated with running. Other studies in mice have shown that BDNF levels are increased in the hippocampus within 3 weeks of voluntary exercise and levels remain high up to 2 weeks after the end of the exercise period (15). BDNF levels did not return to baseline until after 3-4 weeks after the running period, and the performance in the radial arm maze was best when performed 1 week after the end of running.…”
Section: Molecular Mechanisms Of Adaptive Responses To Oxidative Stressmentioning
confidence: 81%